Today's woman: looking for new proyects : Vocational/occupational counselling for middle-aged women - Salazar, Mara (2005)
The present work has been prepared taking into account the nature and development of the programme “Today's Woman: looking for new projects”, that is being carried out by the Centre of Vocational/Occupational Counselling within the Secretary of Extension Studies in the Faculty of Humanities and Educational Sciences at the National University of La Plata. This programme, which was started in 1999, is one of the permanent activities of the Centre, which is under the Directorship of Dr Mirta Gavilán, constitutes an innovative step in the field of Counselling, insofar as it addresses the situation of women in the 45 to 60 years-of-age group. Given that this group of women requires a particular search which must be associated with better future perspectives, specialized counselling is required as well as group follow-up treatment to share, elaborate and redefine the situation they are going through and thus, to generate the changes that are needed for the realization of new projects and enterprises. For the development of this issue, we present a descriptive abstract of the programme and its development, as well as some conclusions and reflections that may be used as a basis for new proposals This issue about women, which is in constant evolution, makes it impossible to be conclusive, but must be construed as a starting point for new lines of thought and interpretations within the framework of vocational/occupational counselling and the targeted population. The consulted bibliography encompasses a variety of Works concerning the subjects of counselling, women, and current social contexts. It is a bibliographic selection that may be used as a reference in the theoretical and practical development of a Women's Workshop.